Law, Journalistic Profession and Mass Media Ethics - M. Yoserizal Saragih (Budapest International Research and Critics University, 2021)
In law and mass media studies, morals and ethics are linked to the obligations of journalists, such as; the implementation of journalistic code of ethics in every journalistic activity is subject to legal institutions and regulations to carry out with good etiquette as the provisions in the law, which are a set of principles and rules that have generally been accepted and approved by the public. In this regard, ethical principles for the journalistic profession provide a legal basis for managing news in the media in an orderly manner in the relationship between legal subjects. In developments in media institutions in Indonesia, the aspects of share ownership in the media (leadership), economics and media marketing will greatly determine the ideology that is promoted by the media, where this ideology, if it leads to a political economy approach, will create media actors who are less familiar with communication ethics. Communication ethics here are positioned as mere instruments and become less meaningful in determining program content, program quality and media actors' respect for human rights that are represented by individuals as sources of information. This choice raises communication ethics on media actors who are considered to have experienced a reduction. Media players as a profession have taken a shortcut by referring to the principle of benefit, prioritizing the principle of benefit in its coverage and news, which is also paradoxical with the professional ethics it carries. To make matters worse, the absence of respect for the presumption of innocence in the name of the public's interest in obtaining information will increasingly make the mass media and media actors as dominant persons in reconstructing and manipulating social reality. Up to this point, the choice of the tendency to interpret the political economy approach or the ethical approach, in fact both of them do not have obvious legal implications, all of them are returned to each individual who is involved in activities in mass media institutions.